2020
DOI: 10.1016/j.annepidem.2020.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed diabetes among immigrant and racial/ethnic minority adults in the United States: National Health and Nutrition Examination Survey 2011–2018

Abstract: Undiagnosed diabetes disproportionately affects medically underserved groups. It is unknown whether being an immigrant confers additional risk for undiagnosed diabetes. Purpose: To examine independent associations of immigrant status and race/ethnicity with the prevalence of diagnosed and undiagnosed diabetes in a U.S.-based population sample. Methods: Respondents were 21,306 adults from the 2011-2018 National Health and Nutritional Exam Survey.Immigrant status was coded as foreign-born or U.S.-born. Six racia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Recent research has revealed high prevalence but low awareness of cardiometabolic disease among African immigrants in the U.S. [8,9]. Other studies of African immigrants living in high-income settings have found low levels of health insurance [10] and linkage to primary care [11,12] as well as low or delayed uptake of vaccination [13,14], cancer screening [15,16], antenatal care [17], and diabetes screening [18]. Therefore, identifying and addressing specific barriers to engagement in preventive health care (defined here as proactive measures taken to prevent or mitigate future illness) is needed to improve health outcomes of African immigrant populations in the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has revealed high prevalence but low awareness of cardiometabolic disease among African immigrants in the U.S. [8,9]. Other studies of African immigrants living in high-income settings have found low levels of health insurance [10] and linkage to primary care [11,12] as well as low or delayed uptake of vaccination [13,14], cancer screening [15,16], antenatal care [17], and diabetes screening [18]. Therefore, identifying and addressing specific barriers to engagement in preventive health care (defined here as proactive measures taken to prevent or mitigate future illness) is needed to improve health outcomes of African immigrant populations in the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…Crude and adjusted analyses showed that non-US citizens had 41% and 38% higher odds, respectively than US citizens to receive SLKT (Figure 2 and Figure 3, respectively). The results could be related to the higher prevalence of comorbid advanced CKD in non-US citizens with ESLD due to higher incidence of diabetes [33], lower private insurance coverage rates [34][35][36], and delayed access to dialysis [37].…”
Section: Discussionmentioning
confidence: 99%
“…The foreign-born population participates in the labor force at a high rate but also faces systemic obstacles to accessing and utilizing health care. As a result, this population may be less likely to receive a diagnosis for objective health measures such as type 2 diabetes or heart disease (Bacon, Riosmena and Rogers 2017; Barcellos, Goldman and Smith 2012; Hsueh et al 2020). Thus, an encompassing health indicator such as self-reported number of sick days may provide immigration and health researchers an additional and alterative measure of health.…”
Section: Discussionmentioning
confidence: 99%